"Don't do vape, bro!" A qualitative study of youth's and parents' reactions to e-cigarette prevention advertisements. (January 2021) - Popova, Lucy; Fairman, Robert T.; Akani, Bangaman; Dixon, Kristin; Weaver, Scott R.
Highlights: Evaluations of e-cigarette prevention messages are lacking. We qualitatively assessed youth's and parents' reactions to anti-e-cigarette ads. Information on chemicals in e-cigarettes was seen as new and scary. Messages featuring diverse real youth are needed. Abstract: Introduction: Growing rates of e-cigarette use among youth have reached epidemic proportions. Media messages have been deployed to counteract this trend, but their evaluations are lacking. We assessed youth's and parents' reactions to various existing e-cigarette prevention messages. Methods: In 2019, 12 focus groups were conducted with youth (n = 63) and parents (n = 27). Participants discussed their reactions to 9 existing messages with various topics. Results: Information on chemicals in e-cigarettes was seen as new and scary, but unknown chemical names created confusion. Youth appreciated novel ways to visualize health effects of e-cigarettes (parasites in the body) and nicotine's effect on behavior (mood swings), but they cautioned that some of these effects (irritability) are not always caused by nicotine. Some participants did not know if e-cigarette companies were "Big Tobacco." Some found it hard to argue with the financial costs of vaping, but others did not think they were too great. Participants recommended messages featuring testimonials from diverse adolescents and messages aimed at youth who are struggling with addiction to e-cigarettes. Conclusion: Messages would be particularly effective if they featured real youth and did not look like adults created them for youth. Another area that is currently not covered in media messages is talking to youth who are using e-cigarettes and might be already addicted but do not know where to turn for help. These adolescents need to be referred to resources for cessation.